Superintendent Turnover and Retention: A Mixed-Methods Study Of Leavers and Stayers In Rural Districts - David E. DeMatthews; Alexandra Aylward; Torri D. Hart; Pedro Reyes (AERA Open)
Superintendents play a vital role in the districts and communities they serve, which is especially true in many rural contexts that function not only as a site for PreK–12 education but also as a community hub for a range of supports and services. Instability in the role can be threatening to district improvement, but research on the topic has been limited and too often focused exclusively on large districts and relying only on large longitudinal datasets. Our explanatory, sequential mixed methods study begins with an examination of demographics and turnover trends across 600 rural Texas school districts to investigate the realities of turnover in Texas rural superintendency. However, we also identified and interviewed a sample of rural superintendents we classified as “leavers” or stayers” to examine how unique personal factors influence decisions to stay or go. Findings illuminate the multifaceted and idiosyncratic factors that contribute to rural superintendent turnover with implications for policy and leadership preparation and development.